Private law and the UK Supreme Court : key cases and decisions - Russell, Jenny; Graham, Lewis (Editor of UK Public law) (Routledge, 2026)
"This volume brings together expert commentators across different fields of Private Law to comment on a key decision by the UK Supreme Court (UKSC). Each author explores their case's content, as well as its broader implications for private law as a field and the Supreme Court as an institution. The work is divided into the following areas: Tort; Contract and Unjust Enrichment; Property Law and Equity. Providing expert commentary on recent authorities of the highest level in one place, the collection will enable readers interested in these areas to conveniently locate analysis that will aid them in their work. Taken together, the contributions enable identification of themes relating to continuity and change; the role of policy in private law; the structure of private law; neglecting differences in bargaining power; and the Court's relationship with the lower courts. As such, it will be an invaluable resource for academics, researchers, practitioners, judges and policymakers"-- Provided by publisher.
Keywords: Great Britain. -- Supreme Court.; Civil law -- Great Britain.; Civil law -- Great Britain -- Cases.; elektronické knihy; electronic books